Methods of an assessment of investments - Baydildina, A. M. (Journal of Economic Research & Business Administration, 2015)
Consideration of any investment project demands the preliminary analysis and an assessment as a result of which the investor can define degree of appeal of this project by methods of the theory of the investment analysis. In Kazakhstan such methods which were widely adopted around the world, began to be applied rather recently. The assessment of efficiency of investment projects takes the central place in the course of justification and a choice of possible options of an investment of means. Implementation of effective projects increases arriving in the order of society a gross internal product which then shares between subjects participating in the project. For the modern large companies investment projects are one of the most effective ways to survive in the conditions of the rigid competition in the market. At the same time many investment projects quite often are unprofitable. Often it is a consequence of the wrong planning of projects or imperfection of methods of the analysis.